2018
DOI: 10.1108/jhom-06-2017-0120
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of health service management competencies

Abstract: Purpose The importance of managerial competencies in monitoring and improving the performance of organisational leaders and managers is well accepted. Different processes have been used to identify and develop competency frameworks or models for healthcare managers around the world to meet different contextual needs. The purpose of the paper is to introduce a validated process in management competency identification and development applied in Australia - a process leading to a management competency framework w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 43 publications
3
76
0
1
Order By: Relevance
“…The findings contrast to a recent management competency study in Australia targeting senior managers in both public hospitals and community health services [26]. This study confirmed that more than two thirds of the senior managers working in both the public hospitals and community health services in Victoria (one of the largest Australian States) possessed a postgraduate qualification.…”
Section: High Education Level Versus Low Participation Of Management supporting
confidence: 55%
See 1 more Smart Citation
“…The findings contrast to a recent management competency study in Australia targeting senior managers in both public hospitals and community health services [26]. This study confirmed that more than two thirds of the senior managers working in both the public hospitals and community health services in Victoria (one of the largest Australian States) possessed a postgraduate qualification.…”
Section: High Education Level Versus Low Participation Of Management supporting
confidence: 55%
“…Although management competencies are context sensitive [25], the literature confirms the existence of core competency requirements across management levels and positions [26][27][28]. Hence a competency framework identified in one healthcare context can be applied to other contexts after being tested.…”
Section: Introductionmentioning
confidence: 99%
“…There was general agreement amongst participants that in order to be a successful manager of integrated care, both aspects, learned behaviour and innate personality, were important, thus echoing the discussions in more recent management theory that both intrinsic and extrinsic factors make good managers [56,58]. Whilst some managers had a more natural leaning towards integrated care, it was thought that all could develop the necessary competences with personal commitment and a supportive environment.…”
Section: Management Of Integrated Carementioning
confidence: 78%
“…The question of what makes a good manager has interested philosophers and statesmen throughout the ages. Whilst there is recognition that the demands made on a manager will vary dependant on the context and their particular role, considerable work has been done to clarify what competences are required by managers within healthcare settings [13,18,28,30,31,49,56]. Pihlainen et al (2016)'s [57] systematic review suggests that competences related to the healthcare context have social, organisational, and financial dimensions, and that these should be demonsrated alongside operational (i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The University had a long running successful Master of Health Administration (MHA) program for Australian managers. The La Trobe MHA program was particularly attractive to the Chinese health managers for its practice orientated approach designed around a validated management competency framework [details about the competency framework have been published elsewhere, (8)(9)(10)]. La Trobe University (LTU) draws many Asian students.…”
Section: Background and Rationalementioning
confidence: 99%